Implementasi Profil Pelajar Pancasila Dalam Upaya Atasi Degradasi Moral - Galuh Dwi Anindyawati (Prosiding Temu Ilmiah Nasional Guru, 2022)
The form of a nation's success to achieve its goals will be largely determined by the quality of its human resources. Pancasila as the basis of the state that contains the values, norms and philosophy of life of the nation needs to be implemented or implemented in order to overcome various student characters whose moral quality is currently decreasing. Pancasila is a way of life. Students' character and morals are not formed simply and instantly, but still through habituation and continuous practice. Moral degradation in students that is happening at this time really needs the planting and application of Pancasila values. Therefore, the purpose of this research is to understand the emergence of the phenomenon of moral degradation in the younger generation and it can be handled appropriately. The method that the author chooses in this research is a qualitative method which, the author collects data based on a literature study. The expected result of this article is that values ​​can be embedded that can stimulate the growth of positive behavior in the school environment. The inculcation of Pancasila values ​​which is the basis of the nation's life that needs to be understood and applied in everyday life. As we know, Pancasila can be used as the basis for thinking, the basis for behaving, behaving and acting. That way, the younger generation will have moral values ​​and noble character